A Theoretical Study on the Hydrogenation of CO Over Co2Cu2 Bimetallic Catalyst Supported on MgO(200) by Means of Density Functional Theory Part 1: Adsorption and Activation Stages - Long, Nguyen Binh; Thu Ha, Nguyen Thi; Lan, Phung Thi; Cam, Le Minh; Ha, Nguyen Ngoc (VNU Journal of Science: Natural Sciences and Technology; Vol 36 No 1DO - 10.25073/2588-1140/vnunst.4995, 2020)
Density functional theory (DFT) at GGA-PBE/DZP level was performed to study the adsorption processes of CO and H 2 on clusters Co 2 Cu 2 and Co 2 Cu 2 supported on MgO (Co 2 Cu 2 /MgO) system. The electronic structures, geometries of Co 2 Cu 2 and Co 2 Cu 2 /MgO, adsorption energies were studied and analyzed. The optimal adsorption configurations of CO and H 2 on Co 2 Cu 2 and Co 2 Cu 2 /MgO were determined. The results show that CO and H 2 are chemically adsorbed on Co 2 Cu 2 and Co 2 Cu 2 /MgO systems and the adsorption process does not involve a transition state. MgO support plays important role in the increasing of the activation ability of Co 2 Cu 2 /MgO for CO compared to the initial cluster. Keywords : Syngas, DFT, Co 2 Cu 2 , MgO, adsorption.